Differential memory and executive functions in demented patients with Parkinson's and Alzheimer's disease. Issue 1 (January 1991) - Litvan, I; Mohr, E; Williams, J; Gomez, C; Chase, T N
Abstract : Selected aspects of verbal memory and executive function were compared in 11 demented Parkinson's disease (PD) patients and 11 Alzheimer's disease (AD) patients with equally severe dementia, with 11 healthy controls matched for age and education. Semantic and episodic memory were impared in all patients compared with controls, but to a relatively greater degree in AD patients than in those with PD. In contrast, demented PD patients were relatively more compromised on executive tasks. These findings, taken in the context of the neuropathological and neurochemical overlap between demented PD and AD patients, suggest that differences in neurobehavioural patterns in patients with these diseases are relative, rather than absolute.